From the classical art to the urban art infusion effect: The effect of street art and graffiti on the consumer evaluation of products - Carsten Baumgarth; Jennifer Bahati Wieker (Creativity and Innovation Management, 2020)
Combinations of art and products are a classic and current topic. Examples like the collaboration of the Medici with artists in the Renaissance or the logo development of Chupa Chups by Salvador Dali are historical examples. The BMW art cars by Jeff Koons and Cao Fei or the art-based special editions of Louis Vuitton bags are current best practices. All these cases expected a positive impact of art on the product or brand evaluation. This spillover effect was coined “art infusion effect” by Hagtvedt and Patrick. This, as well as further studies on the art infusion effect, are predominantly concerned with classical fine arts. However, despite an observable increase of urban arts-brands collaborations, the effects of these have not been researched. Our study determines that graffiti and street art are perceived by consumers as art. To confirm the art infusion effect for urban art, a laboratory experiment was conducted. The presence of urban art has a favourable influence on the evaluation of products. These results replicate and extend the findings of Hagtvedt and Patrick. As drivers of the urban art infusion effect, we also identify two additional drivers: the fit between the art and the product and the “lifestyle perception”.
Keywords: 330; art infusion effect; arts-brand collaborations; graffiti; street art; urban art